(untitled) (Palíndromo, 2019)
The work of the artist Paulo Gaiad reveals narratives between fiction and biography, in plots that are woven by images and words, which tell a series of real and imaginary events, recorded by memory and reinvented by imagination, places, travels and landscapes. In this way, we intend to take a look at the narrative elements of the artist based on approximations and distances, with the hybrid creation process of the artistic languages, inserted in the contemporary scenario. Moreover, the narrative elements in the artist’s work are presented against the destruction of memory, present in the immediacy of daily life and in slavery imposed by work, which belongs to the very characteristic of experience in contemporary life.